The Integration of the Engineering Design Process in Biology-related STEM Activity: A Review of Thai Secondary Education - Krittin Tipmontiane; P John Williams (Universitas Pendidikan Indonesia (UPI), 2022)
STEM education is an effective instructional approach to multidimensionally develop students. Although the engineering discipline (E) in STEM education is ambiguously represented and integrated in the field of biological concepts in secondary education, the engineering design process (EDP) is showing potential to clearly guide educators to incorporate the EDP in biological classes. Thus, this review paper proposes to offer ideas of integrating EDP into biology-related STEM lessons in the context of Thai secondary education. It also outlines benefits and challenges of EDP integration which may assist teachers during designing lessons. The gathered results of prior research suggest that the EDP has potential to provide experiences focused on multidisciplinary real-life circumstances via hands-on activities in order to investigate solutions to problems. The challenges are greater to integrate EDP into biological tasks than other disciplines because of the nature of the content. Due to the ambiguity of integration, professional development programs, the implementation of suitable life-science content, and biological inspiration would assist teachers in conducting high-quality biological STEM activities which incorporate EDP. Moreover, time constraints, teachers’ negative attitudes, and a lack of resources should be addressed as barriers to consider before the implementation.